2018
DOI: 10.1089/cyber.2018.0045
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Game Induces Active Engagement on Neuromuscular Electrical Stimulation Training in Patients with Stroke

Abstract: This study aimed to investigate the effectiveness of the mobile game-based neuromuscular electrical stimulation (MG-NMES) with assessing usability issues, such as attention and curiosity, and intrinsically interesting issues, which is necessary for successful poststroke rehabilitation. With the conventional NMES (C-NMES) system, the subjects underwent active repetitive cyclic NMES training. For assessment of usability issues, 20 hemiplegic stroke subjects were randomly divided into two groups. The subjects in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…They expect to foster the engagement through the gamification of the therapeutic exercises and at the same time give the therapist the possibility to control and customize the levels of complexity of the rehabilitation training. Seven of the ten included studies measured flow experience in the context of serious games in patients with stroke, PD, MS and/or TBI [42][43][44][45][46][47][48]. Flow experience was mainly assessed in the context of usability studies in newly developed serious game therapy programs for rehabilitation purposes [42,43,45,47].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They expect to foster the engagement through the gamification of the therapeutic exercises and at the same time give the therapist the possibility to control and customize the levels of complexity of the rehabilitation training. Seven of the ten included studies measured flow experience in the context of serious games in patients with stroke, PD, MS and/or TBI [42][43][44][45][46][47][48]. Flow experience was mainly assessed in the context of usability studies in newly developed serious game therapy programs for rehabilitation purposes [42,43,45,47].…”
Section: Discussionmentioning
confidence: 99%
“…Flow experience was mainly assessed in the context of usability studies in newly developed serious game therapy programs for rehabilitation purposes [42,43,45,47]. Our review showed that total flow mean scores between 3.76 and 4.33 points on a 5-point Likert scale were achieved in all studies when serious games were used as physical-therapeutic exercises [42][43][44][45][46] compared to control groups without serious games, these flow mean points reached 3.65-3.76 [44,46]. It turns out that therapeutic interventions with a game-like character stimulate concentration and enjoyment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data representing physiological responses to being hit and weapon fire such as saturation of blood oxygen, breathing behaviour, heart rate and so on are provided as a feedback for communication with the wearer by means of ARAIG. Jeonghun Ku [5] performed rehabilitation of post-stroke patients by assessment of intrinsically interesting issues, curiosity, attention, usability issues and so on with the help of neuromuscular electrical stimulation (MG-NMES) based mobile games.…”
Section: Existing Literaturementioning
confidence: 99%
“…It is essential for stroke affected patients to relearn performing the basic motor activities [5]. Practice and feedback and provided to enable learning and to improve its efficiency.…”
Section: Introductionmentioning
confidence: 99%